Peranan Guru Dalam Membimbing Siswa Yang Melakukan Perilaku Bullying Di SD Negeri 3 Suak Lamatan Kabupaten Simeulue - Lauhil Maulindah; Mislinawati Mislinawati; M. Husin (Universitas Syiah Kuala, 2023)
The role of the teacher is as an organizer of the learning environment as well as a learning facilitator. This role requires that planning is always adapted to the conditions of the students, students' study habits, experience and knowledge of students, various learning methods and subject matter according to students' learning interests. The teacher does not only act as a provider of information to students but a complex action. Bullying behavior is caused by several factors, namely seniority, family, personality, school, social environment, television and print media, lack of self-confidence, wanting to be popular, and lack of empathy. The formulation of the problem in this research is